Extensive preclinical evaluation of combined mangiferin and glycyrrhizic acid for restricting synovial neovascularization in rheumatoid arthritis - Xia Mao; Xiangying Yan; Congchong Li; Yudong Liu; Yanqiong Zhang; Na Lin (BMC, 2023)
Abstract Background Synovial neovascularization promotes rheumatoid arthritis (RA) progression. Baihu guizhi decoction (BHGZD) has a potential in restricting this pathological change of RA. Purpose To identify bioactive compounds (BACs) of BHGZD and to elucidate the underlying mechanisms in restricting synovial neovascularization of RA. Method Through transcriptomic profiling, the chemical profiling of BHGZD and its effective transcriptomic profiling against RA were identified. Then, candidate targets and the corresponding BACs against synovial neovascularization were screened by "disease gene-drug target" interaction network analysis and in silico molecular docking. The binding affinities of candidate BAC-target pairs were verified using surface plasmon resonance, and the pharmacokinetic characteristics of BACs in vivo after BHGZD administration at different time points were detected by Ultra Performance Liquid Chromatography-Mass spectrum/Mass spectrum. After that, in vivo experiments based on adjuvant-induced arthritis (AIA-M) rats, and in vitro experiments based on human umbilical vein endothelial cells (HUVEC) and arthritic synovial fibroblasts (MH7A) were carried out to evaluate the pharmacological effects of BHGZD and the two-BACs-combination, and to verify the associated mechanisms. Result VEGFA/VEGFR2/SRC/PI3K/AKT signal axis was screened as one of the key network targets of BHGZD against synovial neovascularization in RA. Mangiferin (MG) and glycyrrhizic acid (GA) were identified as the representative BACs of BHGZD for their strong binding affinities with components of the VEGFA/VEGFR2/SRC/PI3K/AKT signal axis, and their high exposed quantity in vivo. Both BHGZD and the two-BAC combination of MG and GA were demonstrated to be effective in restricting disease severity, reducing synovial inflammation and decreasing the formation of vascular opacities in AIA-M rats, and also reducing the migrative and invasive activities of HUVEC and MH7A cells and attenuating the lumen formation ability of HUVEC cells significantly. Mechanically, both BHGZD and the two-BAC combination markedly reduced the expression of VEGFA in synovial tissues, the serum levels of VEGF and NO, and the enzymatic activity of eNOS, increased the content of endostatin, and also reversed the abnormal alterations in the VEGFA/VEGFR2/SRC/PI3K/AKT signal axis in vivo and in vitro. Conclusion MG and GA may be the representative BACs of BHGZD for restricting excessive synovial vascularization in RA via regulating VEGFA/VEGFR2/SRC/PI3K/AKT signal axis.